Cannabis use in patients with insomnia and sleep disorders: Retrospective chart review. (May 2022) - Vaillancourt, Régis; Gallagher, Shannon; Cameron, Jameason D.; Dhalla, Rahim
Background: Medical cannabis has been increasingly used in Canada after being sanctioned by Health Canada in 2001. Insomnia and sleep disorders are among the most common conditions for which patients report using cannabis. Current research shows cannabis may have a beneficial effect in sleep disorders and may improve patient-reported sleep scores. Methods: A retrospective chart review was conducted at Hybrid Pharm community pharmacy in Ottawa, Ontario, and included patients who were interested in, or already using, medical cannabis for sleep disorders. A qualitative, exploratory approach was taken to evaluate the descriptive efficacy and safety of medical cannabis when prescribed for insomnia or comorbid conditions. The comprehensive data collection also involved investigating the impact of cannabis on other medication used for insomnia. Results: A total of 38 patients were identified as having adequate follow-up documentation to assess the impact of medical cannabis. At time of data collection, 15 patients (39%) were able to reduce or completely discontinue a prescription medication indicated for sleep. On follow-up, 27 patients (71%) reported a subjective improvement in their sleep or related condition. Only 8 patients (21%) reported any adverse effects from medical cannabis use, and these were manageable and did not require discontinuation of cannabis. Conclusion: This study highlights the importance of a pharmacist's role in the management of cannabis-based therapy, including ongoing supportive care, follow-up and medication management. Can Pharm J (Ott) 2022;155:xx-xx.